Free trade today - Bhagwati, Jagdish N. (Princeton, N.J. : Princeton University Press, 2002)
The book punctures all the standard false arguments for protection and he uses the modern theory of commercial policy to suggest how a balanced approach to trade and social policy might look.
Includes bibliographical references and index.
opc 28/09/2016
Loans
Keywords: Free trade; Free trade--Environmental aspects; Free trade--Social aspects; International economic relations; United States of America